Hypoxia-mediated histone acetylation and expression of N-myc transcription factor dictate aggressiveness of neuroblastoma cells - Poljaková, Jitka; Groh, Tomáš; Gudino, Zaneta Omana; Hraběta, Jan; Bořek-Dohalská, Lucie; Kizek, René; Doktorová, Helena; Eckschlager, Tomáš; Stiborová, Marie (Oncology reports, 2014)
Cells of solid malignancies generally adapt to entire lack of oxygen. Hypoxia induces the expression of several genes, which allows the cells to survive. For DNA transcription, it is necessary that DNA structure is loosened. In addition to structural characteristics of DNA, its epigenetic alterations influence a proper DNA transcription. Since histones play a key role in epigenetics, changes in expression levels of acetylated histones H3 and H4 as well as of hypoxia-inducible factor-1α (HIF-1α) in human neuroblastoma cell lines cultivated under standard or hypoxic conditions (1% O2) were investigated. Moreover, the effect of hypoxia on the expression of two transcription factors, c-Myc and N-myc, was studied. Hypoxic stress increased levels of acetylated histones H3 and H4 in UKF-NB-3 and UKF-NB-4 neuroblastoma cells with N-myc amplification, whereas almost no changes in acetylation of these histones were found in an SK-N-AS neuroblastoma cell line, the line with diploid N-myc status. An increase in histone H4 acetylation caused by hypoxia in UKF-NB-3 and UKF-NB-4 corresponds to increased levels of N-myc transcription factor in these cells.
Keywords: regulace genové exprese u nádorů; Gene Expression Regulation, Neoplastic; Neuroblastoma; histony; western blotting; lidé; Histones; neuroblastom; Proto-Oncogene Proteins c-myc; Cell Hypoxia; Acetylation; Blotting, Western; protoonkogenní proteiny c-myc; Cell Line, Tumor; hypoxie buňky; nádorové buněčné linie; acetylace; Humans